1994
DOI: 10.1128/aac.38.12.2803
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of electrical enhancement of efficacy of antibiotics in killing biofilm bacteria

Abstract: The bioelectric elfect, in which electric fields are used to enhance the efficacy of biocides and antibiotics in killing biofilm bacteria, has been shown to reduce the very high concentrations of these antibacterial agents needed to kill biofilm bacteria to levels very close to those needed to kill planktonic (floating) bacteria Work in many laboratories (16,17,32), including our own (3,12,33), has clearly established that biofilm bacteria are resistant to antibiotics and biocides at levels 500 to 5,000 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
196
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(205 citation statements)
references
References 38 publications
(82 reference statements)
2
196
1
Order By: Relevance
“…Ultrasound [51][52][53] and electric fields [54][55][56] have been used to enhance the efficacy of antibiotics in killing biofilm bacteria in sterilization processes. Ultrasonic irradiation enhanced the killing of P. aeruginosa in biofilms by gentamicin by nearly two orders of magnitude [51,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound [51][52][53] and electric fields [54][55][56] have been used to enhance the efficacy of antibiotics in killing biofilm bacteria in sterilization processes. Ultrasonic irradiation enhanced the killing of P. aeruginosa in biofilms by gentamicin by nearly two orders of magnitude [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…O'Leary et al [53] have shown that statistically significant bactericidal effects of ultrasonic irradiation upon pure cultures of the periodontal pathogens P. gingivalis and A. actinomycetemcomitans were due to the incidental temperature increase [53]. On the other hand, small direct current electric fields achieved a 6-to 8-log increase in killing after 24 hours of exposure to the direct current using biofilms of P. aeruginosa [54][55][56]. An electric current enhanced the efficacy of gentamicin against the oral microorganism Streptococcus gordonii in an in vitro biofilm model [57].…”
Section: Discussionmentioning
confidence: 99%
“…One approach is the use of catheters coated with antimicrobial agents alone, or in combination with the passage of a low voltage electric current [31]. The generation of electrolytes such as protons, hydroxyl anions, reactive oxygen intermediates, oxygen and hydrogen appears to enhance antibiotic killing of bacterial cells attached to the device surface and is termed the bioelectric effect [9].…”
Section: Future Developmentsmentioning
confidence: 99%
“…New polymers (e.g. Vivathiane), resorbable biomaterials (polyglycolic and polylactic acid), special coatings (hydrogels, silver, chlorhexidine, antibiotics, surlactin biosurfactant) or the addition of electric current have been shown to reduce bacterial colonization of medical devices in vitro [18, 19, 20, 21, 22, 23, 24, 25, 26, 27]and, alone or in combination, offer a variety of possibilities to eliminate the problem of colonization in future.…”
Section: Discussionmentioning
confidence: 99%